Global up-to date emissions using the EDGAR Fast-Track methodology - Diego Guizzardi; William Becker; Federico Pagani; Marilena Muntean; Monica Crippa (Scientific Data)
Abstract One of the goals of the Paris Agreement is to regularly collect knowledge on the collective effort of abating global greenhouse gas (GHG) emissions. However, national emission inventories submitted to the UNFCCC only partly provide this information, due to the limited time series completeness and time lag compared to the current year. Developing up-to date global GHG emission inventories is therefore essential to enable the assessment of global GHG emission trends and to contribute to the 5-years cycle of the global carbon stocktake as foreseen by the Paris Agreement. The Emissions Database for Global Atmospheric Research (EDGAR) fills this knowledge gap, providing on an annual basis reliable and up-to date independent estimates of global CO2 and non-CO2 GHG emissions with a minimum delay (t-1), for all countries and sectors. This work describes the approach developed and applied within EDGAR to compute emissions up to the most recent year, thus making EDGAR a reliable and timeliness source of information for assessing the collective effort towards climate targets.